Insurance Literacy Among Gen Z Women: Financial Literacy and Education Level as Mediating Variables - Latif, Abdul; Apriani, Erna; Hartati, Nani; Afandi, Dian Rachmawati (Global Financial Accounting Journal, 2025)
Gen Z, as the demographic bonus generation, certainly has an important role to play. The number of independent women today can rival the number of male workers, making women a benchmark for economic growth. From this phenomenon, Gen Z women in Indonesia's journey towards a golden Indonesia in 2045 must understand and use insurance products for long-term protection. Based on this background, this study aims to examine several aspects: first, the direct role of financial literacy on insurance literacy; second, the direct Influence of financial literacy on Education level; third, the direct impact of Education level on insurance literacy; and fourth, the mediating role of Education level in the indirect relationship between financial literacy and insurance literacy. The research method employs a quantitative causal approach, with a sample of Gen Z women in Bekasi Regency using purposive sampling with 100 respondents. Data analysis techniques utilize SEM PLS (Structural Equation Modeling – Partial Least Squares) with the SmartPLS statistical tool. The results of the study found that financial literacy and Education level directly and significantly Influence insurance literacy. In contrast, financial literacy directly and significantly influences Education level, and Education level mediates the relationship between financial literacy and insurance literacy